Low birth weight and birth weight status in Bangladesh: A systematic review and meta-analysis - Shaikh Saijuddin; Islam Md. Tanvir; Campbell Rebecca K. (Anthropological Review, 2021)
The prevalence of low birth weight (LBW) is high in Bangladesh, but no study has collated recent estimates of LBW prevalence from throughout the country. The aim of this meta-analysis was to evaluate the prevalence of LBW and birth weight status in Bangladesh. We searched PubMed, Medline, Ovo and Google Scholar to find published articles in national and international journals from 2000–2020 and reviewed for relevance. Meta-analysis and Q test were performed to estimate the prevalence and heterogeneity of LBW from all included articles. Meta-regression was done to quantify associations with sample size and study year. Stratified analysis was conducted and effect size calculated for differences in LBW prevalence by sex, division and urban/rural area. In total 48 studies with 166,520 births were found and included in this meta-analysis. The pooled prevalence of LBW was 29.1% (95% CI, 28.9–29.3%) in overall, 29.9% (29.7–30.2%) in rural and 15.7% (14.9–16.6%) in urban areas. There was no significant difference in average birth weight between boys and girls (SD, 0.71; 95% CI, −0.43–1.83). Prevalence of LBW was higher in north-east Bangladesh compared to other zones (p<0.05). The pooled prevalence of LBW did not change significantly for last two decades. The prevalence of LBW in Bangladesh remains high. Lack of improvement suggests an urgent need for scaled up maternal and prenatal interventions and services known to reduce LBW. Urban/rural and divisional differences in rates suggest areas of greatest need.